The agents of industrial policy and the North-South convergence: State-owned enterprises in an international-trade macroeconomic ABM - Lucrezia Fanti; Marcelo C. Pereira; Maria Enrica Virgillito (Global Labor Organization (GLO), 2024)
How to conceive industrial policies as development instruments distinct from trade or fiscal-deduction interventions? How can we model and study the role of state-owned enterprises (SOEs) as agents of industrial policy? How can we model their main attributes and architectures? Drawing on the labour-augmented K+S agentbased model (ABM) in a two-country configuration, we propose an ABM aimed at analysing how SOEs may affect technological and industrial development, fostering economic growth and international competitiveness, in the context of a North-South, leader-laggard type of dynamics. Our objective is not simply to study the ex post outcomes of industrial policies, but rather to model SOEs as explicit economic agents potentially capable to drive industrial dynamics, institutional build-up, and, ultimately, growth. The results indicate that SOEs are a relevant policymaking instrument for these purposes.
Keywords: C63; J3; E24; O1; 330; Industrial Policy; State-Owned Enterprises; Technology Gap; Agent-Based Model